Development of Used Cooking Oil Circulation Reactor for Biodiesel Production as Learning Media of Vocational Mechanical Engineering Student - Hartono, Rudi; Denny, Yus Rama; Ramdani, Sulaeman Deni; Assaat, Lusiani Dewi (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to develop and test the feasibility of a waste cooking oil-based biodiesel reactor prototype media used as a learning medium with a circulation system. The method in this research is Research and Development using the Waterfall model. The stages in the waterfall development model are (1) requirements definition including (needs analysis, analysis of used cooking oil characteristics, analysis of renewable energy, hardware requirements), (2) implementation and unit testing, (3) integration and system testing including: (testing the reactor, and testing the appropriateness of the media and materials), (5) operation and maintenance include: (testing the biodiesel reactor to students ). The research subjects were three lecturers as material expert validators and media experts and ten mechanical engineering vocational students as users to test the product's feasibility. The research results are as follows; development of biodiesel reactor media and results of feasibility research by media experts got an average score of 4.48 with the category